Ways to increase the efficiency of budget for the general education - E. B. Krylova; V. A. Gnevasheva; M. V. Belyaeva (Путеводитель предпринимателя)
This article discusses ways to improve the efficiency of budget spending on general education in the Russian Federation, found reserves for the optimization of budget expenditures in the field of general education, refined approach and the principles of their effective use.